Rethinking social justice - Anandhi, S.; Manoharan, Karthick Ram (ed.); Vijayabaskar, M. (ed.); Kalaiyarasan, A. (ed.) (Hyderabad Orient Blackswan Private Limited, 2020)
The discourse of social justice has been much contested in India ever since the time of the Mandal Commission report. Nearly four decades on, debates on culture and identity remain strong. Rather than studying the concept of social justice in isolation, in distinct social, political or economic terms, Rethinking Social Justice offers a more transdisciplinary approach to envisioning a just society that encompasses the intersecting issues of caste, capital, nationalism, gender, region, urban planning and visual representation. Divided into five broad thematic sections Politics of Culture and Identity; Critical Social History; Nation and the Region; Political Economy; and Cinema and Society this volume brings together perspectives from across disciplines to rethink the question of social justice, in the process opening up a view of the panorama of Indian politics. This collection is an homage to M. S. S. Pandian who, through his writings on political economy, Dravidian politics, film studies, and social and intellectual history, interrogated questions of caste, identity and cultural elitism in his broader quest for social justice. In this volume, eminent scholars friends and colleagues of Pandian enter into a dialogue with Pandian s life-work, cut short by his untimely demise in 2014. They build upon his legacy to not only critically evaluate politics and society, but also subject mainstream culture to an equally critical evaluation. Social scientists, activists, journalists, policymakers and film critics will find immense value in this insightful collection of essays
Contributed articles.
Includes bibliographical references.
Keywords: Social justice; Social justice